Dokument a fabuła – refleksje, doświadczenia i metody pracy autora zdjęć filmowych - Staroń, Wojciech (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
As the very title of Wojciech Staroń, a cinematographer and film director’s text “Documentary versusfiction – reflections, experiences and work methods of a director of photography” indicates, it is an attempt to analyse his own artistic achievements combined with a theoretical reflection on universal and fundamental issues such as understanding the truth in film, in reference to the distinction between the genres of fiction and documentary, or mentioned towards the end of the text, an issue of constructing a film protagonist and film narration in which the protagonist functions and is immersed. All these issues are analysed in a visual context, in reference to the construction of a film shot – the meaning of its contents and form and their combination which will present the subject matter in a few seconds of screen time. The films being analyzed among others are: Pod ochroną, Nagroda and Argentyńska lekcja (Argentinian Lesson).